Increasing training effectiveness through strengthening Instructor Competence, Training Design, Training Environment, Training Materials and Achievement Motivation - Ningsih, Wilia; Setyaningsih, Sri; Irdiyansyah, Iyan (Dinasti Publisher, 2025)
This study aims to produce a strategy to improve the effectiveness of training through strengthening the variables of instructor competence, training design, training environment, training materials as independent variables and achievement motivation variables as intervening variables. A population of 685 resulted in 253 samples taken by proportional random sampling in 9 Fields of Expertise of Business and Tourism Vocational High School Teachers Participants in the BBPPMPV Business and Tourism Upskilling and Reskilling Training. This study used a survey method with a path analysis approach and SITOREM analysis. The results of this study can be concluded: 1) There is a significant positive direct effect between instructor competence, training design, training environment and achievement motivation on training effectiveness (Y); There is a significant positive direct effect between instructor competence, training design, training environment and training on achievement motivation; There is a significant positive indirect effect between instructor competence, training design, training environment and training materials on training effectiveness through achievement motivation. Achievement motivation cannot mediate instructor competence, training design, training environment on training effectiveness. The results of the SITOREM analysis show that the indicators that are still weak and need to be improved are: 1. interpersonal skills, 2. clarity of training objectives, 3. alignment of learning components, 4. learning support, 5. visual and interactive quality, 6. up-to-date and accuracy, 7. challenging objectives, 8. results orientation, 9. response to feedback, 10. learning support, 11. participant involvement, 12. learning, 13. reaction.